MRI brain in monohalomethane toxic encephalopathy: A case report - Deshmukh, Yogeshwari S (Medknow Publications & Media Pvt Ltd, 2013)
Monohalomethanes are alkylating agents that have been used as methylating agents, laboratory reagents, refrigerants, aerosol propellants, pesticides, fumigants, fire-extinguishing agents, anesthetics, degreasers, blowing agents for plastic foams, and chemical intermediates. Compounds in this group are methyl chloride, methyl bromide, methyl iodide (MI), and methyl fluoride. MI is a colorless volatile liquid used as a methylating agent to manufacture a few pharmaceuticals and is also used as a fumigative insecticide. It is a rare intoxicant. Neurotoxicity is known with both acute and chronic exposure to MI. We present the characteristic magnetic resonance imaging (MRI) brain findings in a patient who developed neuropsychiatric symptoms weeks after occupational exposure to excessive doses of MI.